Three‐Dimensional Fruit Tissue Habitats for Culturing Caenorhabditis elegans. Issue 11 (12th November 2021) - Guisnet, Aurélie; Maitra, Malosree; Pradhan, Sreeparna; Hendricks, Michael
Abstract: Environmental factors influence many traits of biological interest, but reproducing an animal's natural habitat in a controlled laboratory environment is challenging. Environmental enrichment—adding complexity to the usually simplistic conditions under which laboratory animals are raised—offers a potential tool for better understanding biological traits while maintaining controlled laboratory conditions. For the model nematode Caenorhabditis elegans, the contrast between the natural environment and the laboratory conditions in which they are raised is enormous. Although several methods have been developed in an effort to complexify C. elegans laboratory conditions, there is still a need for an enriched controlled laboratory habitat in which C. elegans can be raised over several generations, the bacterial food availability is similar to that in traditional agar plates, and the animals are crawling as opposed to swimming or burrowing. To this end, we describe here a standardized protocol for creating controlled, reproducible, three‐dimensional environments for multigenerational maintenance of C. elegans in the laboratory. These environments are derived from decellularized apple hypanthium tissue and have bacterial food uniformly distributed throughout. We also describe how traditional C. elegans methods of collecting synchronized eggs, cleaning contaminated stocks, and collecting animal populations are adapted to our scaffold environment. These methods can be adapted to host different bacteria or bacterial populations, and the resulting scaffolds can be used in a range of experimental designs for behavioral and phenotypical studies in C. elegans and other nematodes. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Decellularization and storage of apple tissue Basic Protocol 2 : Preparation of plates from decellularized apple scaffolds Basic Protocol 3 : Synchronization of eggs or animals and cleaning contaminated stocks from scaffold plates Alternate Protocol : Collection of non‐synchronized larvae and adults from scaffold plates